Joseph in Egypt : a cultural icon from Grotius to Goethe - Lang, Bernhard (Yale University Press, 2009)
Introduction -- Joseph as a cultural icon in early-modern times -- Joseph in Genesis -- Post-biblical traditions the icon of piety : Joseph for children -- On education -- A lesson in godliness -- Lavater -- Starting life with Joseph -- Goethe appendix : Joseph portrayed -- Trautmann the icon of chastity : the handsome Hebrew -- On sexual morality -- Libertine libido -- Mrs. Rowe -- Irresistible eros -- Bodmer -- The triumph of chaste love -- Fielding the icon of leadership : Joseph the statesman -- On statecraft -- Civic humanist -- Grotius -- Competent courtier -- Zsen -- Hebrew freemason -- Albrecht against the icon : radical readings -- On historical criticism -- Despotic ruler -- Morgan -- Tax collector -- Voltaire the iconic text : a beautiful story -- On literary criticism -- A conte philosophique -- Voltaire -- The triumph of beauty -- Chateaubriand